Very Low Prevalence of Intracranial Hypertension in Trigonocephaly. Issue 1 (January 2017) - Cornelissen, Martijn J.; Loudon, Sjoukje E.; van Doorn, Frida E. C.; Muller, Rogier P. M.; van Veelen, Marie-Lise C.; Mathijssen, Irene M. J.
Abstract : Background: Trigonocephaly is caused by metopic suture synostosis. It is treated by fronto-orbital remodeling, not only to correct the deformity but also to prevent intracranial hypertension, the reported prevalence in trigonocephaly of which ranges from 0 to 33 percent. To support treatment analysis and the design of a treatment protocol for intracranial hypertension in these patients, the authors wished to more accurately quantify the prevalence of preoperative and postoperative intracranial hypertension in a large patient cohort. Methods: The authors included all trigonocephaly patients born between 2001 and 2013 who had all been operated on at a single center. During follow-up, the presence of intracranial hypertension was evaluated by funduscopy, and occipitofrontal head circumference was measured. The occipitofrontal head circumference curve was analyzed and its relation to intracranial hypertension assessed. Results: In total, 262 patients with trigonocephaly were included. Before surgery, 1.9 percent of them had intracranial hypertension; after surgery, 1.5 percent did (mean age at last follow-up, 4.9 years). Sixteen of 176 patients (9 percent) had occipitofrontal head circumference curve stagnation, which was significantly related to intracranial hypertension ( p = 0.001, Fisher's exact test). Conclusions: Intracranial hypertension occurs only sporadically in patients with metopic suture synostosis. Occipitofrontal head circumference measurement should take a prominent place in the postoperative follow-up of metopic suture synostosis patients; stagnation of the occipitofrontal head circumference requires additional screening for intracranial hypertension. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.